2020
DOI: 10.1136/bcr-2020-240088
|View full text |Cite
|
Sign up to set email alerts
|

Brief psychotic disorder associated with quarantine and mild COVID-19

Abstract: A 30-year-old man with no significant previous or family psychiatric history became severely anxious about his health after a positive COVID-19 test. Physical symptoms of COVID-19 were mild, with no evidence of hypoxia or pneumonia, throughout his illness. He was admitted to a quarantine facility. He remained highly anxious, and 1 week later, he developed paranoid delusions and auditory hallucinations (his first psychotic episode). He was treated with lorazepam 1 mg four times a day, mirtazapine 30 mg nocte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 18 articles did not include individual level data and 7 articles were available as abstracts only. A total of 40 articles met inclusion criteria, comprising 48 individual patients from 17 countries ( Table 1 ) [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] ]. All but a single study [ 54 ] were in English and 20 (42%) cases were reported in the United States, where the largest proportion of these cases were documented.…”
Section: Resultsmentioning
confidence: 99%
“… Possible concomitant delirium. Haddad, et al 2020 [ 39 ] 30, M, QA Developed anxiety after positive COVID-19 test, followed by paranoid delusions and AH 1 week later. Mild symptoms of COVID-19 were anosmia and ageusia Anxiety None +SARS-CoV-2 PCR.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Smith et al, the patient developed symptoms of BPD after four days of onset of symptoms of COVID-19 [11]. In another report by Haddad et al, the patient developed BPD after seven days of being diagnosed with COVID-19 [8]. The case series in Italy also showed BPD in patients during the COVID-19 pandemic [12].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, self-isolation, infection, and associated psychosocial stressors such as financial burden and job insecurity secondary to the pandemic can contribute significantly to psychotic symptoms, especially in vulnerable people. Steroids frequently used in the treatment of severe COVID-19 infection may be another potential cause of psychosis in such patients [2,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Although these factors could explain the exacerbation of mental illness or new onset of symptoms, the literature suggests that COVID-19 infection itself can trigger activation of mental illness in susceptible individuals. Previously, a few case reports have described psychosis as a direct consequence of COVID-19 infection [6][7][8][9][10][11]. We describe a patient with no prior history of mental illness developing severe psychosis after contracting COVID-19.…”
Section: Introductionmentioning
confidence: 97%